2019
DOI: 10.3390/toxins11040210
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Isokinetic Training and Botulinum Toxin Type A on Spastic Equinus Foot in Patients with Chronic Stroke: A Pilot, Single-blind, Randomized Controlled Trial

Abstract: Botulinum toxin A (BoNT-A) has been shown effective for poststroke lower limb spasticity. Following injections, a wide range of multidisciplinary approach has been previously provided. The purpose of this pilot, single-blind, randomized controlled trial was to determine whether BoNT-A combined with a regime of a four-week ankle isokinetic treatment has a positive effect on function and spasticity, compared with BoNT-A alone. Secondly, the validity of the use of an isokinetic dynamometer to measure the stretch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…Latino et al observed a similar trend in patients with MS [ 22 ]. This finding is consistent with existing literature showing that the maximum benefit of BoNT-A treatment in the management of spasticity is the association with multi-modal rehabilitation [ 57 , 58 , 59 ]. The underlying mechanism is that physiotherapy in combination with BoNT-A injections can improve the overall response to toxins, likewise by enhancing its diffusion and leading to more effective uptake by the target muscles [ 60 ].…”
Section: Discussionsupporting
confidence: 92%
“…Latino et al observed a similar trend in patients with MS [ 22 ]. This finding is consistent with existing literature showing that the maximum benefit of BoNT-A treatment in the management of spasticity is the association with multi-modal rehabilitation [ 57 , 58 , 59 ]. The underlying mechanism is that physiotherapy in combination with BoNT-A injections can improve the overall response to toxins, likewise by enhancing its diffusion and leading to more effective uptake by the target muscles [ 60 ].…”
Section: Discussionsupporting
confidence: 92%
“…Multiple international focal spasticity guidelines state that “focal spasticity does not always require pharmacological treatment,”55 so the challenge in clinical decision-making is to determine the contribution of factors including focal muscle spasticity, muscle paresis, and reduced motor control that need to be prioritized for treatment. It may be possible that previous studies that failed to make clinically significant improvements in kinematic variables or walking speed following BoNT-A injection had injected muscles with focal spasticity that were not the primary cause of the targeted variable 19–24…”
Section: Discussionmentioning
confidence: 99%
“…It may be possible that previous studies that failed to make clinically significant improvements in kinematic variables or walking speed following BoNT-A injection had injected muscles with focal spasticity that were not the primary cause of the targeted variable. [19][20][21][22][23][24] The calf muscles are the most commonly injected with BoNT-A for focal muscle spasticity in the lower limb, 54 and were the most commonly affected in this current cohort. It is somewhat surprising that although more than half of the participants with TBI had focal calf muscle spasticity, there were no significant differences between those with calf spasticity, those without, and the HC cohort for ankle dorsiflexion at initial contact and during swing (Tables 1 and 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking the total number of adult stroke patients into account, 10-20% have equinus foot as a severe consequence and >90% of patients with RA have reported foot complaints during the course of the disease such as hallux valgus (65%), longitudinal arch (42%) flattening, and claw toe (39%) (3)(4)(5)(6)(7). This is one of the most dysfunctional deformities with a significant impact on gait and quality of life of individuals who have suffered from stroke or RA (5,6,(8)(9)(10)(11)(12). The possible treatment for these dysfunctions/deformities is the use of ankle-foot orthoses (AFOs) or, in severe cases, surgical intervention.…”
Section: Introductionmentioning
confidence: 99%